Spore salutes Mr. Soares - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Mr Álvaro Soares de Melo, the compiler of all 41 editions of our Portuguese-language edition, Esporo, retires with this issue. He has worked in agriculture for several decades; first in his native Azores Islands, where he ran rural radio services,...